Psychological Factors and Customer Satisfaction at Retail Stores in Jaffna Market - Shivany, S.; Vaishanvai, S.; Vinothini, R.; Thadsaniya, I.; Vimalini, V.; Suvithika, S.; Keerthika, S. (The International Institute of Knowledge Management (TIIKM), 2017)
Marketing starts with the needs of the customer and ends with his satisfaction. Consumer is the one who consumes the goods and services produced. The psychological factors are the factors that about the psychological of on individual that drive. His actions to seek satisfaction. Some of the important psychological factors are perception, motivation, learning, attitude and beliefs. Customer satisfaction dissatisfied customer will probably cut their relationship with be engaged in negative word of mouth advertisement will directly affect a company's maintenance and profitability. The satisfied customer will probably talk about their experiences with others who then will be engaged in positive verbal word of mouth (oral) advertisement. Customer satisfaction is the important phenomenon in the retail business; psychological factors have the major influence on customer satisfaction. This paper is probably the first to explore the link between psychological factors and customer satisfaction in Jaffna in retail store contexts. Convenience sample of Jaffna retail customers surveyed using a self-administered questionnaire. Through the quantitative methodology, data were collected from 120 retail customers in Jaffna retail market. Descriptive and inferential statistical were used to analysis the data. Finding shows that psychological factors contributes to customer satisfaction at retail sector. Even though motivation, perception, learning and attitude are contributing to customer satisfaction. Motivations at this retail stores are boosting in creation of customer satisfaction at retail stores. Therefore, this study has a practical implication for managing motivational factors in this retail sector.
Keywords: Customer satisfaction; psychological factors and retail stores